Substrate and temperature effects on the germination of Dypsis leptocheilos (Hodel) Beentje & J. Dransf. (Arecaceae) seeds - Pimenta, R. S. [UNESP]; Batista, G. S. [UNESP]; Gimenes, R. [UNESP]; Pivetta, K. F.L. [UNESP]; Mazzini, R. B. [UNESP]; Romani, G. N. [UNESP] (International Society for Horticultural Science (ISHS), 2012)
Dypsis leptocheilos is highly valued as an ornamental palm. Its propagation is done by seeds; however, there is little information about this process. The objective of this work was to study the substrate and temperature effects on the germination of D. leptocheilos seeds. The experiments were carried out at FCAV/UNESP, Campus of Jaboticabal, Sao Paulo State, Brazil. In order to study the substrate effects, four treatments were arranged (coconut fiber, sand, vermiculite and Plantmax®) at 30°C. For the temperature effects, six treatments were performed (temperature at laboratory conditions (21.5°C and 72% RU), 25°C, 30°C, 35°C, 20-30°C and 25-35°C), having the coconut fiber as the substrate. The experimental design was completely randomized, with four replicates of 25 disseminules per plot (seeds with attached endocarp). Water replacement was managed to maintain 100% of the retention capacity of the substrates. The germination tests were observed every two days, and conducted over 148 days for the substrate effects, and over 152 days for the temperature effects, when no more seed germination was noted. In order to determine the germination percentage (% G) and the Germination Speed Index (GSI), the seed was considered germinated when the germinative button appeared. At the end of the experiments, leaf area (cm2), root and shoot length (cm), root and shoot dry mass (g) were also obtained. Statistical analysis was performed and means were compared by the Tukey test. Germination rate and speed in coconut fiber was higher at 25 and 30°C. However, when other substrates were tested at 30°C, the highest germination percentage was observed in vermiculite, which also sustained better results for the seed germination and for the characteristics related to shoots and roots.
Keywords: Palm; Propagation; Seedling